University students' knowledge, attitude, and practice KAP towards COVID-19 in Malaysia - Mohd Zubir, Zur Batrisyia; Abd Rahaman, Nor Yasmin; Awang Hamat, Rukman; Kadir @ Shahar, Hayati (Universiti Putra Malaysia, 2021)
Covid-19--associated with the human-to-human transmission is recent medical concern which also associated with public health concerns. A cross-sectional online survey was conducted among clinical year veterinary and medical students studying in a university in Malaysia to determine the students' knowledge, attitude, and practice towards COVID-19. The questionnaire consisted of 4 sections, namely, socio-demographic characteristics (6 items), knowledge (14 items), attitude (10 items), and practice (24 items) towards COVID-19. The collected data were subjected to descriptive statistics, Mann-Whitney U, Kruskal-Wallis H, and Spearman's correlation analysis. A total of 219 students participated in this study, and they consisted of 52.1% and 47.9% of veterinary and medical students, respectively. The total scores were categorised into poor (<60%), moderate (60-79%), and high (>80%) based on Bloom's cut off point. Overall, the students acquired high knowledge (80%), moderate attitude (76%) and high practice (86%) against COVID-19. In the attitude section, the veterinary student scored significantly higher than medical students (U=3791, p= .001), and female students scored significantly higher than males (U=3183, p= .001). The analysis revealed a statistically significant association between attitude and practice (P< .05) despite no association between knowledge to attitude and practice variables. Overall, the results indicated that both veterinary and medical students had high knowledge with moderate to high attitudes towards COVID-19. Thus, they were practising good preventive measures in limiting the spread of the disease.